ICT at COP21 : Enormous Potential to Mitigate Emissions - Gallegos, Doyle (World Bank, Washington, DC, 2016)
The transformational potential of new information and communication technologies (ICTs) was on display in Paris at the Twenty-First Conference of the Parties (COP21) to the United Nations Framework Convention on Climate Change. ICTs, including the Internet, mobile phones, geographic information systems (GIS), satellite imaging, remote sensing, and data analytics, could reduce yearly global emissions of carbon dioxide (CO2) 20 percent by 2030, thus holding them at their 2015 level. Moreover, ICT emissions are expected to decrease to 1.97 percent of the global total by 2030, from 2.3 percent in 2020, while emission reductions attributable to ICT will be nearly 10 times greater than those of the ICT sector. ICTs are also critical for climate change adaptation, providing vital tools for all phases of the disaster risk management cycle. Although the opportunities for ICTs to support the climate change agenda are enormous, much work remains in order to realize them. Governments of developing countries must be further encouraged to include ICTs in their national climate change policies. And the international development community will have to make significant efforts, particularly in low-income countries, to develop ICT infrastructure as well as the institutional capacities and skills to implement and sustain these solutions.